IMPLEMENTASI PENDIDIKAN KARAKTER MELALUI BUDAYA SEKOLAH PADA SISWA SEKOLAH MENENGAH KEJURUAN - Nindi Virgustina (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2019)
This study was aimed the implementation of character education through school culture including; planning, implementation, evaluation and the inhibiting factors and supporting in implementing character education. The type of This research was qualitative research. Data was obtained from interviews, observation and documentation. The validity of the data was done by triangulation. The use of Data analysis techniques by: (data reduction), (data display), (verification). The results : (a) Character education planning has been carried out with the guidance of order books. (b) The implementation of character education has been carried out indicated by the school culture that is used for students students have a better character. (c) Evaluation of character education for students has been carried out, with morning activities, evaluation of teachers and employees on Thursday at 6:00 WIB. Supporting factors, support from the school community, but there are still students who disobey the rules.